Immunomodulatory effects of dietary β-glucan in silver catfish (Rhamdia quelen) - Domenico,Janine Di (2017)
ABSTRACT: The immunomodulatory effects of dietary β-glucan were evaluated in silver catfish. β-glucan was added to the diet (0.01%, and 0.1%) and fed to the fish for 21 days, to evaluate effects on blood and some innate immune parameter, or fed for 42 days, to evaluate growth rate and resistance to challenge with pathogenic Aeromonas hydrophila. We found that adding β-glucan to the diet had no effect on fish growth and no effect on blood cells, or serum bacterial agglutination and serum myeloperoxidase activity. However, fish that received β-glucan in the diet had the natural hemolytic activity of complement significantly higher compared to control fish. Furthermore, fish fed with β-glucan and challenged with A. hydrophila had fewer bacteria in blood and presented a significantly higher survival rate compared to control fish. Thus, we concluded that β-glucan might be explored as feed additive aiming to improve silver catfish innate immunity and resistance to specific pathogen.